UBEZPIECZENIE SPOŁECZNE ROLNIKÓW POLSKICH NA TLE DOŚWIADCZEŃ WYBRANYCH KRAJÓW UNII EUROPEJSKIEJ - Tryfan, Barbara (Wydział Prawa i Administracji UAM, 1999)
Polish farmers dispose of their own system of insurance including annuities, pensions for retired and medical care. We should ask in what degree this system is compatible with occidental solutions, further - if it does assure a decent existence for the elderly of the country and, finally, if it stimulates changes in agrarian structure. Demographic old age in the EU countries is accompanied as a rule with good organisation of medical care and high living standard, whereas Polish country men - characterised with an advanced process of the ageing - suffer from too many lacks in the sphere of social and technical infrastructure, are confronted with difficulties in labour market organisation, shortages in social help and, last not least, are largely subject to a disparity in farmers’ income in comparison with other social and professional groups. The Institute of the Country Development and Agriculture of the Polish Academy of Sciences has inaugurated in 1998 an empirical research of the system of social insurance for the farmers as involved with the process of European integration. The research object was a public opinion poll on functioning of the present system, what shall enable to take into consideration its results in order to get perfected the set of principles for to adept them successively to regulations in force in the EU countries.
SOCIAL INSURANCE OF POLISH FARMERS AGAINST THE BACKGROUND OF EXPERIENCES IN SOME CHOSEN COUNTRIES OF THE EUROPEAN UNION